Parenting Patterns and Elementary School Children's Achievement Motivation - Desi Nur; Roby’ Ultrianda; Nabila Maharani; Nanda Aqilah (International Journal of Educational Research, 2024)
This study aims to describe the relationship between parenting styles and achievement motivation in elementary school children. Using a descriptive qualitative approach, the research analyzes various literature and secondary data sources to provide an in-depth understanding of how different parenting styles influence children's motivation to learn. The findings show that democratic parenting has the most positive impact on children's achievement motivation, characterized by two-way communication, emotional support, and responsible freedom. In contrast, authoritarian and permissive parenting styles tend to hinder children's motivational development. This study emphasizes that the synergy between appropriate parenting, a supportive learning environment, and active parental involvement significantly contributes to improving children's motivation and academic performance in elementary school.